Photovoltaic - Battery Operated Electric Vehicle with an Energy Management Strategy. Issue 1 (February 2021) - Gomathy, S.; Sabarimuthu, M.; Krithika Sree, S.; Radha, J.; Vennila, R.; Krishna, M.P.
Abstract: Hybrid energy storage systems have many advantages, including the use of multi-input converters, such as reduced part count, flexibility power, and absolute control of energy sources. In these systems, an Energy Management Strategy must wisely determine the power levels of the sources. Energy management strategy for photovoltaic/ battery including a bidirectional multiple - input converter electric vehicle is presented in this article. The proposed Energy management strategy not only regulates the state-of-charge of photovoltaic. The battery power profile is also smoothed by using a fuzzy controller and a rate limiter. Since the energy transfer between battery and Photovoltaic is free in this multi-input converter. This results in a hybrid energy storage system that is sustainable and has improved battery life. The feasibility of the proposed system is systematically tested by a simulation study and an observational framework involving an actual electric vehicle. In this paper the results proves that Energy Management Strategy for photovoltaic including electric vehicle is presented. The enhancement of the battery cycle-life is discussed because of the battery / PV hybridization based on experimental performance.